2020
DOI: 10.3390/insects11070402
|View full text |Cite
|
Sign up to set email alerts
|

It Is Not All about Being Sweet: Differences in Floral Traits and Insect Visitation among Hybrid Carrot Cultivars

Abstract: Cytoplasmically male-sterile (CMS) carrot cultivars suffer from low pollination rates. In this study, insect visitation varied more than eightfold between 17 CMS carrot cultivars in a field-based cultivar evaluation trial. The visitation rates of honey bees, nectar scarabs, muscoid flies, and wasps each significantly differed among these cultivars. No significant difference in visitation rates was observed among cultivars of different CMS type (brown-anther or petaloid) or flower colour, but cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
3
8
0
1
Order By: Relevance
“…In agreement with previous studies (Gaffney et al ., 2020), we show that the sugar levels and composition in our samples varied greatly between individuals, but no significant difference between accessions was observed. Our results show that sugars, and thereby reward quality was not linked to the observed differences in bee attraction between the accessions.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with previous studies (Gaffney et al ., 2020), we show that the sugar levels and composition in our samples varied greatly between individuals, but no significant difference between accessions was observed. Our results show that sugars, and thereby reward quality was not linked to the observed differences in bee attraction between the accessions.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we used a comprehensive approach to identify specific traits affecting honey bee attraction to parental accessions and open-pollinated carrot flowers. Considering the need for cross-pollination, only traits present in both male-sterile and fertile parent accessions, such as nectar and floral volatiles (but not pollen), were targeted (Gaffney et al ., 2020). The results from our initial field bioassays suggested that the carrot nectars were not only lacking in attraction but were in fact repelling bees from the feeders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the need for cross-pollination, only traits present in both male sterile and fertile parent accessions, such as nectar and floral volatiles (but not pollen), were targeted. 57 The results from our initial field bioassays suggested that the carrot nectars were not only lacking in attraction but also were in fact repelling bees from the feeders. These observations guided us to develop a new laboratory bioassay protocol, based on the concept by Kessler et al, 71 in which we were able to evaluate the combined effect of odor and taste.…”
Section: ■ Discussionmentioning
confidence: 96%
“…The effects of color and floral morphology have been studied for bee pollination of carrots, with inflorescence color and nectar sugar composition and concentration found not to differ significantly between hybrid lines. 57,58 However, no comprehensive studies of the role of specific volatiles have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%